2008
DOI: 10.1027/1015-5759.24.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Response Processes on Personality Items Using Unfolding and Dominance Models

Abstract: Abstract. Stark, Chernyshenko, Drasgow, and Williams (2006) and Chernyshenko, Stark, Drasgow, and Roberts (2007) suggested that unfolding item response theory (IRT) models are important alternatives to dominance IRT models to describe the response processes on self-report personality inventories. To obtain more insight into the structure of personality data, we investigated whether dominance or unfolding IRT models are a better description of the response processes on personality trait inventories constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…That is, items were developed and retained by these firms based on analyses such as item-total correlations, factor analysis, and/or conventional IRT modeling, all of which carry dominance assumptions. Although the studies reviewed above (e.g., Carter & Dalal, 2010;Stark et al, 2006;Tay et al, 2009;Weekers & Meijer, 2008) show that the ideal point model fits data from dominance scales better than dominance models, measures specifically developed under ideal point assumptions (e.g., Chernyshenko et al, 2007) may show even greater gains in variance explained for curvilinear relations that those found here. Future research should explore this possibility as well.…”
Section: Limitations and Future Directionsmentioning
confidence: 45%
See 1 more Smart Citation
“…That is, items were developed and retained by these firms based on analyses such as item-total correlations, factor analysis, and/or conventional IRT modeling, all of which carry dominance assumptions. Although the studies reviewed above (e.g., Carter & Dalal, 2010;Stark et al, 2006;Tay et al, 2009;Weekers & Meijer, 2008) show that the ideal point model fits data from dominance scales better than dominance models, measures specifically developed under ideal point assumptions (e.g., Chernyshenko et al, 2007) may show even greater gains in variance explained for curvilinear relations that those found here. Future research should explore this possibility as well.…”
Section: Limitations and Future Directionsmentioning
confidence: 45%
“…Moreover, they showed the possibility of considerable differences in the top-down rank-order of individuals between dominance and ideal-point IRT scores. Weekers and Meijer (2008) demonstrated that ideal point models showed better fit than dominance models when applied to responses from a Dutch personality inventory as well as responses from a Dutch translation of Chernyshenko et al's (2007) Orderliness scale. In addition, Weekers and Meijer found the correlation between dominance model-estimated person standing on the latent trait continuum (i.e., estimates) and GGUM based estimates to be .98 and .99 for the two scales, respectively.…”
Section: Modeling Conscientiousness Scores: Dominance or Ideal Point?mentioning
confidence: 99%
“…This feature of the model produces a bell-shaped IRC. Stark et al (2006) fit both dominanceand ideal-point models to scales from a wellknown personality inventory (see also Weekers & Meijer 2008). Results indicated that several items operated more consistently with an idealpoint representation than a dominance representation.…”
Section: -Parameter Modelsmentioning
confidence: 95%
“…For non-cognitive constructs, the construct continuum is better understood as various locations , since the “correct” response is simply that which most accurately reflects one’s position along the latent trait. This is reflected in the references to “item location parameters” when IRT is applied to non-cognitive constructs (Reise et al., 2001; Reise and Haviland, 2005; Vittersø et al., 2005; Gomez, 2008; Weekers and Meijer, 2008; Zampetakis, 2010; Reise et al., 2011).…”
Section: Introductionmentioning
confidence: 99%